2007
DOI: 10.1002/mc.20332
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of multiple treatments, and both DNA and RNA direct bindings on, green tea catechins

Abstract: This article reviews two main topics: (1) the synergistic effects of multiple treatments with green tea catechin and (2) the direct binding of (-)-epigallocatechin gallate (EGCG) to both DNA and RNA molecules. Japanese drink green tea throughout the day, so we studied whether multiple treatments of cells with EGCG would enhance the expression of apoptosis-related genes, such as growth arrest and DNA damage-inducible gene (GADD153) and cyclin-dependent kinase inhibitor gene (p21(waf1)): The results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
(35 reference statements)
2
18
0
Order By: Relevance
“…A number of studies (Kuzuhara et al, 2007;Hakim et al, 2008;Kawai et al, 2008) had demonstrated that tea drinking was a protective factor for CRC risk. The most active constituents of green tea were EGCG, which accounted for almost 50% of the total catechin content in green tea extract, and it had very potent antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies (Kuzuhara et al, 2007;Hakim et al, 2008;Kawai et al, 2008) had demonstrated that tea drinking was a protective factor for CRC risk. The most active constituents of green tea were EGCG, which accounted for almost 50% of the total catechin content in green tea extract, and it had very potent antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that galloyl and catechol groups are essential for DNA binding. [34][35][36] Therefore, the structural difference between oligomers and polymers is considered to be an important factor regarding proanthocyanidin's action. Proanthocyanidin differs from all other natural polyphenols by virtue of its polymeric nature.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] The TG38 monoclonal antibody can be further utilized for basic and clinical experiments in cancer prevention, e.g., the monoclonal antibody makes it possible to investigate the metabolism of EGCG in serum and the distribution of EGCG in tissues and cells.…”
Section: Significance Of Anti-egcg Monoclonal Antibody Tg38mentioning
confidence: 99%
“…Moreover, prevention of high-grade prostate intraepithelial neoplasia was recently reported with green tea catechins. 10) Since EGCG was found to bind to numerous target molecules including DNA and RNA, 11,12) we theorized that green tea catechins induce cancer preventive activity mediated through a chaperone-like property. 13) We thus needed to study the bioavailability of EGCG and the presence of catechins in cells and in vivo.…”
mentioning
confidence: 99%